Perancangan Dan Pembuatan Sistem Organic Rankine Cycle (ORC) Dengan Fluida Kerja R-134a - Clinton Naibaho; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Organic Rankine Cycle is a modified power generation system from Rankine Cycle that uses organic working fluid. In this study the working fluid used is R-134a. The ORC system has four main components, namely the evaporator, turbine, condenser and pump. Flate Plate Collector as a component that converts solar energy into heat energy, in this study used a compressor AC type scroll as a turbine. The overall component scheme and system measurement instrumentation have been made in the form of piping instrumentation diagrams. The initial data determined for the design and calculation of the ORC system analysis is the evaporator temperature 90˚C, the temperature of the condenser is 10˚C, the fluid entering the pump is runny with a pressure of 5 bar inlet and entering the turbine under a saturated steam pressure of 12.5 bar, resulting in an efficiency of 6.65%. For the design of Solar Collector the water intake temperature is 50˚C and exits 95˚C, so that the evaporator tube length is produced 14.53 m, 13.89 m condenser and 9.44 m Solar Collector. Solar Collector produce a temperature of 52˚C then turn on the ORC system by adjusting the evaporator and condenser temperature by 95˚C, and 10˚C, the inlet pressure of the 5 bar pump and 5.2 bar turbine, resulting in a system efficiency of 4,29 %.Keywords : Organic Rankine Cycle, Evaporator, condenser, R134a, Design